An Investigation of the Proportion of Banana Corm and Tapioca Flour on the Organoleptic Properties of Crackers and Their Business Feasibility - Justino Mendes Pereira; Celestino Mendes Pereira; Armando Afonso (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
Banana corm is generally regarded as agricultural waste and remains underutilized despite its potential as a value-added food ingredient. This study evaluated the effect of different proportions of banana corm and tapioca flour on the organoleptic properties of crackers and assessed the business feasibility of the product. The experiment employed a single-factor Completely Randomized Design (CRD) with five treatments: A1 (300:700), A2 (400:600), A3 (500:500), A4 (600:400), and A5 (700:300) (banana corm:tapioca flour), each replicated three times. Crackers were prepared by mixing the ingredients with seasonings, followed by steaming, drying, and frying. Sensory quality was evaluated using the hedonic rating scale. Data were analyzed using analysis of variance (ANOVA), and significant differences among treatments were further examined using the Least Significant Difference (LSD) test at the 5% significance level. The best treatment was determined using the De Garmo weighting method. The results indicated that treatment A3 (500:500) achieved the highest overall sensory acceptance, with the best weighted score (1.00). The business feasibility analysis showed that banana corm cracker production is economically viable, with a break-even point (BEP) of 17,795.45 units (USD 2,189.19) and a revenue-cost ratio (R/C ratio) of 1.16.